Community-Based Training on Mindfulness Relaxation Therapy for Reducing Loneliness Among Older Adults at Posyandu Lansia - Mokhamad Nurhadi; Tiara Putri Ryandini; Dyah Pitaloka (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2026)
Loneliness is a common psychosocial problem among older adults that negatively affects mental health, quality of life, and overall well-being. This community service program aimed to improve older adults' knowledge and skills in applying mindfulness relaxation therapy and to reduce loneliness among participants at Posyandu Lansia in Tuban Regency, Indonesia. A participatory training approach using a one-group pretest–posttest design was implemented in September 2025. The program involved 30 older adults and five Posyandu cadres. Activities included health education on loneliness and mindfulness, guided mindfulness relaxation practice, mentoring, and program evaluation. Participants' knowledge was assessed using pretest and posttest questionnaires, practical skills were evaluated through direct observation, and loneliness was measured using the UCLA Loneliness Scale Version 3. The results showed that participants' knowledge increased after the training, with the mean score improving from 61.8 ± 10.5 to 87.4 ± 7.6. More than 85% of participants correctly performed the mindfulness relaxation techniques, and loneliness scores decreased following the intervention. Participants also reported feeling calmer and more confident in managing negative emotions. Mindfulness relaxation therapy is a practical and effective community-based intervention that can be integrated into routine Posyandu Lansia activities to promote psychological well-being and support healthy ageing.